1994
DOI: 10.1111/j.1600-0773.1994.tb00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes‐Induced Changes in the Gi‐Modulated Muscarinic Receptor‐Adenylyl Cyclase System in Rat Myocardium*

Abstract: The inhibitory guanine nucleotide binding regulatory protein (Gi)-mediated muscarinic receptor-adenylyl cyclase system was studied in myocardium from adult male Wistar rats with 10 weeks of diabetes induced by a single intravenous injection of streptozotocin (60 mg/kg). Neither the messenger ribonucleic acid level nor the amount of Gi was changed in the streptozotocin diabetic group as compared to the control group. The activity of the adenylyl cyclase stimulated by guanyliminodiphosphate was decreased by 48% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Our result on the expression of Gαs, not affected by insulin deficiency, was agreeable with the findings of Wichelhaus et al (1994) in the heart ventricles of streptozotocin-induced diabetic rat. The result of no change of Gαi expression in heart of diabetic rat was agreeable with the findings of Fu et al (1994), but differed from the result of Wichelhaus et al (1994). The G protein-coupled signaling pathways initiate a cascade of enzyme activation, such as PKA, PLC, PKC, CaM kinase etc.…”
Section: Expression Of G Proteinssupporting
confidence: 76%
“…Our result on the expression of Gαs, not affected by insulin deficiency, was agreeable with the findings of Wichelhaus et al (1994) in the heart ventricles of streptozotocin-induced diabetic rat. The result of no change of Gαi expression in heart of diabetic rat was agreeable with the findings of Fu et al (1994), but differed from the result of Wichelhaus et al (1994). The G protein-coupled signaling pathways initiate a cascade of enzyme activation, such as PKA, PLC, PKC, CaM kinase etc.…”
Section: Expression Of G Proteinssupporting
confidence: 76%
“…This is supported by the decrease of the effects of G protein activators NaF and guanine nucleotides (GppNHp), and a suppression of GppNHp potentiating influence on the hormone effects. The decrease (about 50 %) of the GppNHp stimulating effect on AC in the myocardium of diabetic rats was described earlier [27]. In the present study, isoproterenol stimulation of GTPbinding of heterotrimeric G proteins in the STZ diabetes model is reduced in the skeletal muscles, and in the heart muscle of rats [28].…”
Section: Discussionmentioning
confidence: 60%
“…The mechanism of increased function of the neuronal M 2 muscarinic receptors in the diabetic rat lungs is unclear. Radioligand bindind studies performed with diabetic heart membranes confirmed a half‐log increase in agonist binding affinity at the M 2 receptor compared to controls (Bergh et al , 1984; Fu et al , 1994), indicating that increased M 2 muscarinic receptor function seen in diabetic rats may be due, in part, to increased agonist binding affinity at the receptor. In diabetic rat hearts, Bergh et al (1984) have suggested increased coupling of muscarinic receptors to G i .…”
Section: Discussionmentioning
confidence: 87%